Functional prostate-specific membrane antigen is enriched in exosomes from prostate cancer cells - LIU, TIANCHENG (D.A. Spandidos, 2014)
Developing simple and effective approaches to detect tumor markers will be critical for early diagnosis or prognostic evaluation of prostate cancer treatment. Prostate-specific membrane antigen (PSMA) has been validated as an important tumor marker for prostate cancer progression including angiogenesis and metastasis. As a type II membrane protein, PSMA can be constitutively internalized from the cell surface into endosomes. Early endosomes can fuse with multivesicular bodies (MVB) to form and secrete exosomes (40–100 nm) into the extracellular environment. Herein, we tested whether some of the endosomal PSMA could be transferred to exosomes as an extracellular resource for PSMA. Using PSMA-positive LNCaP cells, the secreted exosomes were collected and isolated from the cultured media. The vesicular structures of exosomes were identified by electron microscopy, and exosomal marker protein CD9 and tumor susceptibility gene (TSG 101) were confirmed by western blot analysis. Our present data demonstrate that PSMA can be enriched in exosomes, exhibiting a higher content of glycosylation and partial proteolysis in comparison to cellular PSMA. An in vitro enzyme assay further confirmed that exosomal PSMA retains functional enzymatic activity. Therefore, our data may suggest a new role for PSMA in prostate cancer progression, and provide opportunities for developing non-invasive approaches for diagnosis or prognosis of prostate cancer.